Pengaruh Teknologi Human Resource Information System (HRIS) terhadap kinerja karyawan pada Kantor Cabang Utama Pos Bandung - Sribarokah, Putri; Adji, Widwi Handari (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the effect of Human Resource Information System (HRIS) technology on employee performance. This research uses a descriptive approach with a quantitative approach. Analyze causal relationships using hypothesis testing. Data was collected through distributing questionnaires. All 54 employees of KCU Pos Bandung were the population in this study. Data analysis uses validity, reliability, normality and simple linear regression test procedures, correlation coefficients, determining factors and hypothesis testing. The research results show that HRIS Technology influences employee performance at KCU Pos Bandung